1995
DOI: 10.1002/hep.1840220505
|View full text |Cite
|
Sign up to set email alerts
|

T-cell-mediated autologous hepatocytotoxicity in patients with chronic hepatitis C virus infection

Abstract: Virus-specific cytotoxic T lymphocytes (CTLs) have been suggested to be responsible for the liver injuries in patients with hepatitis C virus (HCV) infection. However, there has been no report of direct evidence to substantiate this hypothesis. In this study, we performed in vitro autologous hepatocytotoxicity assay in 45 patients to examine a possible role of CTLs to HCV-infected live cells. The data were correlated with histology activity index of liver biopsy specimens. Lymphocyte subsets and hepatocyte exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 32 publications
3
41
0
3
Order By: Relevance
“…Some reports have indicated that cell-mediated host immunity is likely responsible for hepatic inflammation. 37 Inflammatory cells and hepatocytes will induce activation of hepatic stellate cells to initiate fibrogenesis. Emerging evidence suggests that patients with HCV-related mixed cryoglobulin display a particular immune response to HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have indicated that cell-mediated host immunity is likely responsible for hepatic inflammation. 37 Inflammatory cells and hepatocytes will induce activation of hepatic stellate cells to initiate fibrogenesis. Emerging evidence suggests that patients with HCV-related mixed cryoglobulin display a particular immune response to HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a decrease in the hepatic NK activity of LGLs obtained from non-cancer liver tissues surrounding human hepatocellular carcinoma, and an increase in its activity from non-cancer liver tissues surrounding metastatic liver cancer were shown (14). Furthermore, it has been reported that hepatic NK cells play an important role in the cytotoxicity to autologous hepatocytes in the same manner as cytotoxic T lymphocytes in patients with chronic hepatitis (23,30).…”
mentioning
confidence: 98%
“…Имму-носупрессивная терапия сопровождается норма-лизацией повышенного уровня трансаминаз, а ее отмена -усилением активности ВГС [21]. Нали-чие гепатита при ВГС-инфекции ассоциировано с инфильтрацией печени эффекторными иммун-ными клетками [34]. Миграция Т-клеток в печень индуцируется хемокинами (CXCL10, CXCL9 и CCL5), которые продуцируются инфицированными гепатоци-тами и взаимодействуют с рецепторами CCR5 и CXCR3 на поверхности Т-клеток [2,30].…”
Section: адаптивный иммунный ответ против Hcv инфекцииunclassified
“…У пациентов с ХГС в печени обнаружены IL10-продуцирующие CD8 + T-клетки, которые могут оказывать негативное влияние на антиген-специфические CD8 + T-клетки [34]. Кроме того, одним из главных источников IL-10 и TGF-β яв-ляются регуляторные CD4 + Т-клетки (Treg), спо-собные подавлять пролиферацию Т-клеток и их цитокин-продуцирующую функцию либо непо-средственно, либо через иммуносупрессивные цитокины [59].…”
Section: тклеток при вгсинфекцииunclassified